Gastrointestinal nematode infections in sheep and goats in West Java, Indonesia - ., Beriajaya (Indonesian Journal of Animal and Veterinary Sciences, 2005)
These studies were carried out in three locations representing low, medium and high altitudes in West Java to determine the effects of season, climate, management, growth and mortality on nematode parasitism in sheep and goats. Basically, the animals in each location were divided into treated and untreated groups with anthelmintics. Animals were weighed and faecal samples were collected every 2 to 4 weeks. Haemonchus contortus and Trichostrongylus spp. were the predominant species of gastrointestinal nematodes recovered from faecal cultures. In low altitude areas, faecal egg counts dropped progressively throughout the dry season and rose again with the onset of the wet season. The proportion of H. contortus larvae decreased progressively throughout the dry season and increased with the onset of the wet season, however the opposite pattern occurred with proportions of larvae of Trichostrongylus spp. In medium altitude areas, there was no consistent pattern of rising or falling faecal egg counts associated with fluctuations in rainfall. In high altitude areas, there was a trend for egg counts to increase progressively after the onset of the wet season even faecal egg counts were below 1500 epg. After treated with anthelmintics, faecal egg counts were suppressed to only few eggs in two weeks and then rose again in four week later, however in animals received medicated phenothiazine, mean egg counts were maintained below 500 epg. Treated animals in medium areas maintained low egg counts until the end of the trial. Seasonal fluctuation in weight gain of sheep was observed in low areas. Treated animals had significantly lower mortality than untreated animals but the evidence that parasitism contributed to this mortality is persuasive. It was concluded that nematode parasites cause a significant loss of production in sheep during wet season in coastal regions and in areas of rainfall throughout the year. Â  Â  Key Words: Sheep, Goat, Nematode, Anthelmintic